What is the Seiberg–Witten map exactly? - Kupriyanov, Vladislav G. (Journal of physics A: Mathematical and theoretical)
We give a conceptual treatment of the Seiberg–Witten map as a quasi-isomorphism of differential graded algebras. The corresponding algebras have a very simple form, leading to explicit recurrence formulas for the quasi-isomorphism. Unlike most previous papers, our recurrence relations are nonperturbative in the parameter of non-commutativity. Using the language of quasi-isomorphisms, we give a homotopy classification of ambiguities in Seiberg–Witten maps. Possible generalizations to the Wess–Zumino complexes and some other algebras are briefly discussed.